Achieving High 1H Nuclear Hyperpolarization Levels with Long Lifetimes in a Range of Tuberculosis Drug Scaffolds. Issue 67 (14th November 2017) - Norcott, Philip; Rayner, Peter J.; Green, Gary G. R.; Duckett, Simon B.
Abstract: Despite the successful use of isoniazid, rifampicin, pyrazinamide and ethambutol in the treatment of tuberculosis (TB), it is a disease of growing global concern. We illustrate here a series of methods that will dramatically improve the magnetic resonance imaging (MRI) detectability of nineteen TB‐relevant agents. We note that the future probing of their uptake and distribution in vivo would be expected to significantly enhance their efficacy in disease treatment. This improvement in detectability is achieved by use of the para hydrogen based SABRE protocol in conjunction with the 2 H‐labelling of key sites within their molecular structures and the 2 H‐labelling of the magnetization transfer catalyst. The T 1 relaxation times and polarization levels of these agents are quantified under test conditions to produce a protocol to identify structurally optimized motifs for future detection. For example, deuteration of the 6‐position of a pyrazinamide analogue leads to a structural form that exhibits T 1 values of 144.5 s for 5‐H with up to 20 % polarization. This represents a >7‐fold extension in relaxation time and almost 10‐fold improvement in polarization level when compared to its unoptimized structure. Abstract : The tuberculosis drugs, pyrazinamide, isoniazid and their derivatives have been optimally hyperpolarized using SABRE. Through 2 H‐labelling the drugs and catalysts T 1 lifetimes of over two minutes and ≈20 % polarization have been achieved which opens the door to in vivo assessment.